Distribución de ingresos e indicadores de carencia para las provincias del noroeste argentino (NOA): Distribución de ingresos y medición de carencia - Adriana Fátima Panico; María Cristina Leguizamón; Antonio Raúl García (Atlantic Review of Economics (ARoEc), 2018)
– In this paper, indicators are estimated referring to income distribution and levels of deprivation, which allow knowing aspects of social life, for Tucumán with the intention of comparing them with those of the rest of the provinces of the NOA, at different moments of time. The indicators that were taken into account to analyze the distribution of income are the Kuznets coefficient, which measures the income gap between the highest income decile and the lowest income decile of a population, and the Gini coefficient. As for the calculation of "lack" and "severe lack", an indirect and relative methodology is considered, centered on total family income and family per capita income. The results obtained reveal that the distribution of income in the region in general presents an improvement, but examining the provinces separately, different results are observed. Regarding the lack indicators, they remained relatively stable in the period studied. The data sources are the National Survey of Urban Households (ENHU) from 2010 to 2014, the National Household Expenditure Survey (ENGHo) 2004/05 and 2012/13 and the Permanent Household Survey (EPH) from 2003 to 2014.
Keywords: 330